2019
DOI: 10.3389/fpsyg.2019.00903
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Sexual Dissatisfaction: Differences Among Heterosexual, Bisexual, and Lesbian Women

Abstract: Gender-based differences in body image dissatisfaction are not conclusive. Women’s body experiences and their impact on sexual satisfaction may advance knowledge on how heterosexual, bisexual, and lesbian women internalize heterosexist values. In this study, we quantitatively examined the degree of body image and sexual dissatisfaction experienced by heterosexual, bisexual, and lesbian women, to determine whether body dissatisfaction can predict sexual dissatisfaction. Three hundred and fifty-four women comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 69 publications
5
15
0
5
Order By: Relevance
“…Concerning the cognitive–affective body image component, the higher degree of drive for thinness in HEW compared to HOW is in line with most previous research [e.g., (2629)]. Authors such as Moreno-Domínguez et al (39) and Swami and Tovée (38) reported significant differences in women’s BMI depending on sexual orientation, which they discussed as a potential reason for the variability in the cognitive–affective body image. As HEW, HOW, and BIW did not differ in BMI in the current study, BMI cannot account for the reported differences in drive for thinness.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Concerning the cognitive–affective body image component, the higher degree of drive for thinness in HEW compared to HOW is in line with most previous research [e.g., (2629)]. Authors such as Moreno-Domínguez et al (39) and Swami and Tovée (38) reported significant differences in women’s BMI depending on sexual orientation, which they discussed as a potential reason for the variability in the cognitive–affective body image. As HEW, HOW, and BIW did not differ in BMI in the current study, BMI cannot account for the reported differences in drive for thinness.…”
Section: Discussionsupporting
confidence: 88%
“…In terms of attitudes and emotions towards one’s own body, the majority of recent studies reported a lower degree of body dissatisfaction in HOW than in HEW (3436), although some studies reported similar levels of dissatisfaction in both groups [e.g., (31, 37)]. Notably in this context, some studies did not report any associations between sexual orientation and body mass index (BMI) [e.g., (38, 39)], while others found a higher BMI in HOW compared to HEW [e.g., (34, 40, 41)], which might account for the aforementioned findings (41). Additionally, studies employing such rating scales revealed that HOW prefer a body ideal with significantly more body fat compared to HEW (34, 4244), although again, other studies found evidence of a similar body ideal among women, independent of sexual orientation [e.g., (37)].…”
Section: Introductionmentioning
confidence: 99%
“…There is a broad consensus that heterosexual women experience normative pressure to achieve specific ideal body sizes [22]. However, lesbian and bisexual women remain underrepresented in the literature, with unclear results due to opposing evidence and mixed sampling methodologies [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…There is a broad consensus that heterosexual women experience normative pressure to achieve specific ideal body sizes [22]. However, lesbian and bisexual women remain underrepresented in the literature, with unclear results due to opposing evidence and mixed sampling methodologies [22][23][24]. Data have recently suggested that bisexual women are more likely than women with other sexual orientations to internalize shape/weight overvaluation and body dissatisfaction [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, sexual minority women are not immune from sociocultural standards of beauty and the internalization of negative attitudes toward their bodies (Huxley et al, 2014). Some emerging evidence suggests that the harmful effects of negative body attitudes on women’s sexual wellbeing could differ between heterosexual, lesbian, and bisexual women (e.g., Moreno-Domínguez et al, 2019). Our small sample of sexual minority women prevented a direct test of differences by sexual identity and limits the generalizability of findings to a more sexually diverse sample.…”
Section: Discussionmentioning
confidence: 99%